Kinetika Adsorpsi Zat Warna Metilen Biru Oleh Karbon Aktif Dari Kulit Kemiri (Aleurites moluccana (L) Willd) - Latupeirissa, Jola; Tanasale, Matheis F.J.D.P.; Musa, Sigit Hardianto (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2018)
The adsorption of methylene blue dye by active carbon of hazelnut shell has been done. Through acquired active carbon composing process, where is the hazelnut shell at entry into furnace on temperature 350 for 2 hour, afterwards is cooled and at sieves by sieve 100 mesh. Then by the calsination process in furnace with temperature 450 one was streamed to gas N2 four 2 hours then characterized by X-ray diffraction (XRD) for carbon before activation. The next activated with KOH solution with a concentration 0f 50 four 5 hour, then dried in an ovenat 120â„ƒ for 1 hour and thencharacterized. Weight of the solidacidity before and after activation consecutive (5.3848 x 10-3 dan 42.1554x 10-3) mol g-1. Isotherm adsorption of methylene blue dyes on active carbon was following the Freundlich isotherm. Adsorption kinetics of methylene blue dyes on active carbon in various concentration of hazelnut shell was controlled with temperature variety at 25 and 30 . The result showed that energy activation was kJ mol-1 and a value isg mg-1 menit-1. Adsorption mechanism of methylene blue dyes on active carbon at various concentration of hazelnut shell is chemical adsorption process.